Strategies to Promote African American Church Leadership Engagement in HIV Testing and Linkage to Care - Stewart, Jennifer M. (J Racial Ethn Health Disparities, 2018)
A vital piece in implementing and sustaining HIV testing and linkage-to-care within Black churches is the support of the pastors and church leadership. In order to promote church-based HIV testing and linkage-to-care, we explored pastor and church leaders’ (1) HIV-related knowledge, (2) their perception of congregant and community engagement in HIV-related risks, and (3) the potential role of the church in HIV testing and linkage-to-care. We conducted focus groups with 57 church leaders and 8 interviews with pastors across 6 churches in Baltimore, MD, USA. Conventional content analysis was used to analyze the qualitative data. The leadership demonstrated different levels of knowledge of the need for confidentiality and the HIV testing process and reported that low levels of HIV knowledge among their congregants was related to low perceived risk of contracting HIV. Pastors and church leaders indicated that community members engaged in sexual risk and drug use but denied that any of their congregants engaged in such behaviors. Finally, pastors and church leaders as stated that churches were best suited as HIV service centers. These findings can be used to develop culturally appropriate interventions for pastors and church leaders to be better equipped and willing to incorporate HIV testing and linkage-to-care in their churches.